Transformasi Teologis Politik Demokrasi Indonesia (Telaah singkat Tentang Masyarakat Madani dalam Wacana Pluralisme Agama di Indonesia) - ZA, Tabrani (Al-Ijtima`i: International Journal of Government and Social Science, 2016)
Raised the urgency of the terms are, how the concept of civil society as a societal good that is created in the life of the nation in Indonesia, as the frame of the existing diversity, religion and culture, and political system of Pancasila democracy. Civil society in the context of Indonesian is how to control the formation of communities in the state through institutional self-activity, independence and autonomy, as well as the establishment of an embodiment of a democratic society. In the context of the Indonesian Pancasila principles, and also with a democratic system of governance, and there is this dilemma and think about the ideal, which is between the Islamic faith and respect for the rights and freedom of religion, politics and the state. The presence of Islam in the transformation objective and mainly do the religious rights and political and human resources in line with the agenda, as well as religious harmony. Islam in Indonesia is constructed precisely by turning good value in the social sphere, culture, politics, economy, education, and access to the system, which in this case involves the rules in the management of the nation's life. We need to develop democratic institutions, especially political institutionalization, as well as to ensure the continuity of effective bureaucratic government open and participatory. This paper examines an attempt to briefly try on civil society in the discourse of religious pluralism in Indonesia with the social - political approach.